A comprehensive analysis of blockchain and its applications in intelligent systems based on IoT, cloud and social media. Issue 12 (26th August 2022) - Dahiya, Amrita; Gupta, Brij B.; Alhalabi, Wadee; Ulrichd, Klaus
Abstract: Distributed Ledger Technology (DLT) driven blockchain is currently one of the most promising technology revolutions with enormous potential across a wide range of applications. Distributed ledger is essentially a distributed and encrypted database that can address several concerns pertaining to Internet security and trust with transparency. In fact, the scope of blockchain applications is broadening with each passing day. The exclusive features of safe and transparent data exchange provided by blockchain technology provide compelling arguments for its implementation in a variety of application scenarios. In this paper, we present the comprehensive view of blockchain and its related concepts. Though, there exists intensive research on these domains; however, these fields are still dealing with several security issues, data reliability and storage and scalability. Blockchain has emerged as a critical technology that can address these issues through its features like decentralization, transparency, immutability and auditability. Building trust in distributed systems without the need for authority is a technological advancement that can be well leveraged by domain, like, Internet of Things (IoT), cloud and social media. Technologies like IoT and Cloud computing can be perceived as the trivial ones to get benefitted from the blockchain. However, the integration of social media and blockchain can revolutionize the domains, like, content creating and sharing, fake news scourge, trademarking and rights management. In this paper, we illustrate the integration of blockchain with IoT, cloud and social media and the related issues and challenges. Moreover, we also show some of the major research works done in each domain.